Digital Accounting and Islamic Financial Literacy toward Digital Financial Reporting Adoption: The Mediating Effect of Self-Efficacy - Sri Rahayu; Ahmad Nizam Che Kasim; Widia Astuty; Azwansyah Habibie (Institut Bisnis dan Informatika Kesatuan, 2026)
As digital transformation reshapes financial management practices, understanding the factors that drive the adoption of digital financial reporting among Sharia MSMEs has become increasingly important due to persistent technological, financial, and psychological barriers. This study examines the effects of digital accounting literacy and Islamic financial literacy on the readiness to adopt digital financial reporting, with self-efficacy serving as a mediating variable among Sharia MSMEs in North Sumatra, Indonesia. A quantitative approach using SEM-PLS was applied to data collected from 187 Sharia MSME owners through purposive sampling. The findings demonstrate that digital accounting literacy and Islamic financial literacy positively and significantly influence both readiness to adopt digital financial reporting and self-efficacy. In addition, self-efficacy was found to positively affect readiness to adopt digital financial reporting. The mediation analysis further confirms that self-efficacy significantly mediates the relationships between digital accounting literacy, Islamic financial literacy, and readiness to adopt digital financial reporting. These results indicate that the digital transformation readiness of Sharia MSMEs is determined not only by digital accounting and Islamic financial competencies, but also by business actors’ confidence in their ability to utilize digital technologies effectively.